Physicochemical and electrochemical characterization of CdO/g-C3N4 nanocomposite for the photoreforming of petrochemical wastewater - Thurga Devi, Munusamy; Chin, Sim Yee; Khan, Maksudur R. (Elsevier Ltd, 2021)
Current research involved fabrication of cadmium oxide-graphitic carbon nitride (CdO/g-C3N4) nanocomposite and evaluation of their photocatalytic properties by physical and electrochemical analysis techniques. The X-ray diffraction (XRD) test demonstrated that the nanocomposite consists of graphite and monteponite phases. UV–Vis absorption and photoluminescence (PL) analysis clearly pointed out both the band gap reduction and inhibition in recombination rate of charge carriers. Based on the photoelectrochemical (PEC) analysis, linear sweep voltammetry (LSV) data demonstrated that CdO/g-C3N4 nanocomposite shows higher anodic current (0.57 mA/cm2) under light emission as compared to dark environment (0.02 mA/cm2). This study was also deliberated with proposed mechanism on photoreforming of wastewater reaction scheme.